Team-based primary care practice and physician's services: Evidence from Family Health Teams in Ontario, Canada. (November 2020) - Somé, N.H.; Devlin, R.A.; Mehta, N.; Zaric, G.S.; Sarma, S.
Abstract: Team-based primary care offers a wide range of health services to patients by using interdisciplinary health care providers committed to delivering comprehensive, coordinated and high-quality care through team collaboration. Ontario's Family Health Team (FHT), the largest team-based practice model in Canada, was introduced to improve access to and effectiveness of primary health care services, and was available primarily for physicians paid under blended capitation models (Family Health Organizations and Family Health Networks). Using health administrative data on physicians practicing under blended capitation models in Ontario between 2006 and 2015, we study the impact of switching from non-FHT to FHTs on the production of capitated comprehensive care services, after-hours services, non-incentivized services, and services provided to non-enrolled patients by family physicians. We find that when in FHTs, physicians increase the production of total services and non-incentivized services by 26% and 5% per annum and reduce capitated comprehensive care services by 3.2% per annum. When in FHTs, physicians also see and enroll more patients relative to those practicing in non-FHTs. We find evidence of improved access to physician's services under team-based primary care, but switching to FHTs has no effect on the production of after-hours services and services provided to non-enrolled patients. Highlights: Team-based primary care increases the production of physician's services. Patient enrollment by physicians increases in an interdisciplinary team. Team-based practice reduces comprehensive services and increases other services. Substitution between services by physicians in a team may be due to tasks shifting.